Implication of time equation in mature and immature area of ramp using time driven activity based costing - Mohd Yazid, Abu (Penerbit UMP, 2020)
At present, 28% of world palm oil output and 33% of global exports are accounted by Malaysia. Malaysia has an important role in meeting the rising world demand for oils and fats in the long term as it is a largest producer and exporter of palm oil and palm oil products. In recent times, few problems have actually happened in this plantation which are difficult to establish a time equation for analyzing the variation of activities, the rate establishment is unsuitable to display the connection between resources supplied and the practical capacity and the manager does not have a method for monitoring capacity usage and unused capacity. The aim of this work is to develop the time equation of mature and immature area at ramp for a better accuracy. Time driven activity-based costing (TDABC) is implemented because the time is successfully measured, the idle capacity is correctly determined and the capacity used and the unused capacity are differently listed. This work considers a data in 2017 to develop the solution. This work found that in the mature area from the available capacity utilization, ramp has high unused capacity with 67492.80 min which means the resources should be forecast properly in future. Meanwhile in the immature area, ramp has closest value to the practical capacity with 6667.20 min and RM5667.12 which indicates the company properly utilizes their resources. Therefore, TDABC provides more comprehensive understanding of practical resources and its associated costs while measuring processes and encouraging quality improvement.